Bidirectional actuation of buckled bistable beam using twisted string actuator. (March 2019) - Addo-Akoto, Reynolds; Han, Jae-Hung
A new actuation mechanism using the twisted string concept to trigger the snap-through of a bistable buckled beam to produce an effective on/off bistable actuator is proposed. The twisted string concept combined with a pin utilizes actuation moment to actuate a bistable beam. The required actuation loads are analytically formulated using the Euler–Bernoulli beam model and solved with the proposed solution algorithm. The actuation mechanism is fabricated to meet the 24.3 N mm actuation requirements. A prototype of the actuator was built, and its performance was evaluated. In a unidirectional actuation, an actuator response time of 104 ms was achieved. The overall response time of the actuator is affected by the length of the string. The twisted string mechanism was also placed in an antagonistic configuration to enable bidirectional actuation. The shape of the input voltage signal also affected the bidirectional performance of the actuator. The actuator produced an actuation bandwidth of 2 and 5 Hz with sine and square input voltages, respectively, while generating 10 mm output displacement.